Quizwhizzer como innovación tecnológica para el aprendizaje de los estudiantes del bachillerato técnico en informática de la Unidad Educativa del Milenio Carlos Alberto Aguirre Avilés, periodo académico Octubre 2024 - Marzo 2025 - Aviles Ortega, Angie Mabel (2025)
The present study analyzes the incidence of Quizwhizzer as a technological innovation to optimize the learning of the students of the technical baccalaureate in computer science of the educational unit of the Millennium Carlos Alberto Aguirre during the academic period between October 2024 and March 2025. This platform based on gamification stimulates the active participation of students through interactive activities, which promote motivation, as well as knowledge retention. Determining the effects of this platform on the educational process of students and its implementation can optimize the learning experience and specific aspects that will help to understand and diagnose the current state of learning, identify factors that favor its adoption, design a pedagogical strategy for its integration and assess the results in terms of motivation and academic performance. It is expected that the platform will stimulate students, promote relevant learning and encourage the development of technical and critical competencies needed in a digital context. The primary purpose of the project is to contribute to the educational progress of students, supporting their autonomy and their ability to face the challenges of a world characterized by high technology and competition.